THE LEADERSHIP OF SCHOOL ADMISNISTRATORS IN PAK KRET, NONTHABURI UNDER SECONDARY EDUCATIONAL SERVICE AREA OFFICE 3 - Kettanom, Thasporn; Manasakron, Kasame; Wilachan, Pramual; Chanpensre , Supanya; Charoenrak, Nittaya (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to a study and comparison of the leadership level of school administrators in Pak Kret District. Nonthaburi Province Under the Office of Secondary Education Service Area 3 by studying and comparing the leadership of school administrators. According to teachers’ opinions Classified by qualifications and experiences and recommendations. Quantitative research Population used as teachers in schools in Pak Kret District, 525 people. People using the Craigci and Morgan sampling tables. Samples were determined by stratified random sampling using stratified schools and simple random sampling. The samples were 217 people. The tools used consisted of a questionnaire. It is a tool used to collect information. Data were analyzed with statistical software packages. Statistics used in the research include the validity of the content. Questionnaire sentiment, basic statistics: frequency distribution, percentage, mean, standard deviation. and hypothesis testing statistics, i.e. t-test and one-way analysis of variance. The research tool was a questionnaire. There is a 5-level estimation scale, the consistency index ranges from 0.80 – 1.00 and the confidence value is 0.81. The results showed that leadership of school administrators was at a high level. Teachers with different levels of qualification and experience have opinions on the leadership of school administrators Overall, they were not different. And the recommendation is as follows. Visionary Should be managed according to the situation and set the direction appropriately. Team work give opinions and solve problems efficiently. Aspect of human relations train yourself and solve problems logically. Communication should study and research for clarification on the matter conveyed before communicating.